Research on U Hotel - Sangari Sundaraju; Daisy Mui Hung Kee; Rebecca Dershini Lopez; Yuvamalar Balakrishnan; Youdtha Sagadevan (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
U Hotel Penang is a great choice for accommodation when visiting Penang. With its convenient location, the hotel offers easy access to the cities famous destinations. The hotel offers guests superior services and a broad range of amenities, U Hotel Penang is committed to ensuring that customer stay is as comfortable as possible. This hotel offers numerous on-site facilities to satisfy even the most discerning guest. Urban. Unpretentious. Utterly Unique. Moto of U Hotel which make hotel bright in Penang. Travellers looking for stylish, comfortable and affordable accommodation this hotel built for business travellers, convention-goers, and holiday-makers simply looking to get away. 128 rooms of this hotel are stylish with contemporary interiors designed with an industrial theme with a retro twist. U Hotel is in Bayan Lepas which is known as the heart of Penang’s industrial hub, which is only 15 minutes away from the Penang International Airport and close to the biggest business centres, convention halls, factories and Queensbay mall, one of Penang finest shopping mall. An exceptional experience Penang has to offer, U Hotel will be part of its Wi-Fi is free and special parking spaces for customer. Target customer for U Hotel is family, business persons especially whoever visit Penang for tourist purpose. Penang known for food and best place to enjoy for tourism purpose. This is one of additional benefit to U Hotel to get many customers from everywhere in Malaysia and overseas. The price of accommodation reasonable because it already centre of city so it is based on the environment and demand. U Hotel is 3 star of hotel which perfectly have best facilities as 4-star hotel. In Gelugor there is no other 3-star hotel as U Hotel, so it is only one good hotel for tourist. Then the location of U Hotel is quiet near to airport and it is advantage to tourist whoever lives in U Hotel. Although U Hotel is good in external ways but internal factors there are some problems that organization hard to solve it. One of the problems encounters by this U Hotel is complain of dissatisfaction of wages and special promotion to employee such as discount for them. Then, employees are not getting enough motivation to succeed in their performance. Lastly, job satisfaction that refers to unhappy or negative feelings about the work and work environment. The management and employees must prioritize and plan the most important task in an organized way to reduce stress. Besides, the management must empower and offer more opportunities for advancement to motivate the employees. Finally, job satisfaction can be improved by providing positive working environment, rewards and recognition to the employers and employees.